2021
DOI: 10.3390/pathogens10070913
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Organoids Derived from a Parkinson’s Patient Exhibit Unique Pathogenesis from Chikungunya Virus Infection When Compared to a Non-Parkinson’s Patient

Abstract: (1) Background: Arboviruses of medical and veterinary significance have been identified on all seven continents, with every human and animal population at risk for exposure. Like arboviruses, chronic neurodegenerative diseases, like Alzheimer’s and Parkinson’s disease, are found wherever there are humans. Significant differences in baseline gene and protein expression have been determined between human-induced pluripotent stem cell lines derived from non-Parkinson’s disease individuals and from individuals wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 114 publications
(139 reference statements)
0
8
0
Order By: Relevance
“…Chikungunya virus, an RNA virus from the Togaviridae family, was studied in cerebral organoids derived from Parkinson’s disease (PD) iPSCs and non-PD iPSC derived cerebral organoids. The immune response of PD cerebral organoids was altered compared to the non-PD organoids, highlighting the need for studies on the influence of host genetic variation on host-pathogen interactions [ 95 ]. John Cunningham virus (JCV), a DNA polyomavirus, was studied once in cerebral organoids [ 96 ].…”
Section: Resultsmentioning
confidence: 99%
“…Chikungunya virus, an RNA virus from the Togaviridae family, was studied in cerebral organoids derived from Parkinson’s disease (PD) iPSCs and non-PD iPSC derived cerebral organoids. The immune response of PD cerebral organoids was altered compared to the non-PD organoids, highlighting the need for studies on the influence of host genetic variation on host-pathogen interactions [ 95 ]. John Cunningham virus (JCV), a DNA polyomavirus, was studied once in cerebral organoids [ 96 ].…”
Section: Resultsmentioning
confidence: 99%
“…LACV, according to Winkler et al, diminished CO cell viability and that committed neurons were much more susceptible to LACV apoptosis than neural progenitors, which replicate data from humans, primates and rodents [83,121]. Using COs, Schultz et al found that organoids derived from patients with Parkinson's disease had increased pathology from Chikungunya virus (CHIKV) than organoids derived from normal patients [62]. This is intriguing since recent reports indicate a link between SARS CoV-2 and exacerbated Parkinson's disease [122][123][124].…”
Section: Unguided Organoid Modelsmentioning
confidence: 86%
“…Virus researchers typically present data from brain organoids derived from a single cell line, although some recent studies have derived brain organoids from two unique cell lines [55,[61][62][63][64][65][66]. While dozens of organoids can be produced through a single generation protocol, the resultant organoids are basically clones of each other and donor-specific characteristics persist in unique cell lines.…”
Section: Cell Lines Used For Organoid Generationmentioning
confidence: 99%
“…Scale bar, 500 μm. Reproduced from Schultz et al under the terms of the CC BY license [ 164 ]. Copyright 2021, MDPI.…”
Section: D In Vitro Infectious Viral Disease Model...mentioning
confidence: 99%